Disaster management - Awange, Joseph (2018)
© Springer International Publishing AG 2018. Natural disasters, whether of meteorological origin such as cyclones, floods, tornadoes and droughts or of having geological nature such as earthquakes and volcanoes, are well known for their devastating impacts on human life, economy and environment, and are also formidable physical constraints in our overall efforts to develop and utilize the natural resources on a sustainable basis (Jayaraman, Chandrasekhar, Rao, Acra Astronaut 40(2–8):291–325, 1997, [1]).